Knjižna ocena - Italo Pardo in Giuliana B. Prato (ur.), Citizenship and the Legitimacy of Governance: Anthropology in the Mediterranean Region, Ashgate, Farnham, 2011, 221 str. - Kralj, Ana (Dve domovini, 2022)
.